(untitled) (Research, Society and Development, 2022)
Introduction: Suicide is a global public health problem that has gradually increased in the last 10 years. Brazil occupies the eighth position in the world ranking with the most cases of suicides. The aim of the study is to analyze the effectiveness of government measures to prevent suicide in Brazil. Methodology: This is an integrative literature review carried out through the Scielo, Pubmed, BVS, CINAHL and UpToDate databases containing publications between 2017 and 2022. Results: Between 2010 and 2019, an increase of 43% in the annual number was observed of suicides in Brazil, totaling 112,230 deaths. This data reflects the ineffectiveness of public policies in combating suicide. Associated with the inefficiency of action plans, the lack of specific training of health professionals in primary care hampers the identification and treatment of related diseases. Conclusion: Public policies for suicide prevention must be more precise and effective, so that its practice reaches all citizens. Studies point to a lack of control over these indices and a progressive increase in suicide cases. Interventions related to the first manifestations of suicidal ideation have promising potential as effective measures and should be studied.